"Something Unspeakable": James Baldwin and the "Closeted-ness" of American Power. (4th October 2017) - Jones, David
Abstract : This article reads the work of James Baldwin in dialogue with that of Eve Kosofsky Sedgwick. Taking its cue from Baldwin's claim that Americans "live […] with something in [their] closet" that they "pretend […] is not there, " it explores his depiction of a United States characterized by the "closeted-ness" of its racial discourse. In doing so, the article draws on Sedgwick's work concerning how the containment of discourses pertaining to sexuality hinges on the closeting of non-heteronormative sexual practices. Reconceptualizing Sedgwick's ideas in the context of a black, queer writer like Baldwin, however, problematizes her own insistence on the "historical gay specificity" of the epistemology she traces. To this end, this article does not simply posit a racial counterpart to the homosexual closet. Rather, reflecting Baldwin's insistence that "the sexual question and the racial question have always been entwined, " I highlight here the interpretive possibilities opened up by intersectional analyses that view race, sexuality, and national identity as coextensive, reciprocal epistemologies.